INVESTIGATING IRAQI EFL STUDENT- TEACHERS' ASSESSMENT LITERACY: MATCHES AND MISMATCHES BETWEEN THEIR PERCEPTIONS AND KNOWLEDGE - M. A. Entidhar Neamah Aboalshoon Janabi (American Journals Publishing, 2023)
The success of teaching, the quality of student learning, and the motivation of students to learn all depend on teachers' ability to effectively assess their students. However, studies have repeatedly shown that the levels of assessment literacy for instructors in general education and language teaching are inadequate. The purpose of this research is to gain an understanding of the current level of assessment literacy among Iraq EFL student-teachers as well as to determine the areas in which their assessment knowledge is lacking and where it excels. This investigation makes use of a descriptive quantitative methodology, which includes an assessment knowledge test produced by Farhady and Tavasouli (2018) as well as a teacher's perception assessment test. The outcomes of this research point to both strengths and shortcomings in EFL teacher assessment literacy, as well as matches and mismatches between student-teachers' self-perceived assessment literacy and the demonstrated assessment expertise of their students. Over half of all teachers of English to speakers of other languages believe they have sufficient language assessment competence. Nevertheless, the findings that were gleaned from the two tests suggested that almost two thirds of them lacked the necessary level of literacy in terms of assessment knowledge. According to these findings, it was discovered that there is a large discrepancy between students-teachers' beliefs of their assessment knowledge and the actual level of literacy that they possessed. The study may have some repercussions for EFL teacher preparation programs, teaching institutions, and other future research areas.
Keywords: Language assessment, Language assessment literacy, Formative assessment, Summative assessment.